Social Climber Sebagai Aktualisasi Diri Dimediasi Harga Diri Dan Gaya Hidup Hedonis Terhadap Perilaku Konsumtif - Purnama Sari, Desak Made Febri; Putri Oktapia, Ida Ayu Putu (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
Balinese people, including the people of Sanur, are thick with cultural diversity. Therefore, there is no day without religious activities. Various types of products are needed to support religious activities, for example in terms of fashion. The increasing fulfilment of means of supporting religious activities such as kebaya, kamen, and luxurious and contemporary accessories has become commonplace for women. Creating changes in the social environment by showing that consuming modern and luxurious religious support facilities with a hedonistic lifestyle can increase social status and self-esteem. The purpose of this study is to determine the extent of the role of self-esteem and hedonic lifestyle in modulating the impact of social climbers on consumer behaviour. The study focused on a population of women residing in Sanur. A purposive selection strategy was used to select a sample of 136 respondents. The quantitative research approach involved the use of questionnaires to obtain data. The data analysis methodology used was Structural Equation Model - Partial Least Squares (SEM-PLS). The research findings show that social climbing has an important and positive impact on self-esteem and hedonic lifestyle. In addition, self-esteem has a positive and significant effect on consumer behaviour, while hedonic lifestyle has a negative and significant effect on consumptive behaviour. Furthermore, social climbing has a positive and significant effect on consumptive behaviour. In addition, self-esteem plays an important role in mediating the relationship between social climbing and consumptive behaviour, with a positive and significant effect. Finally, hedonic lifestyle mediates the relationship between social climbers and consumer behaviour negatively and significantly.